Giddens and Bauman: the institutional configurations in the contemporaneity - Ribeiro, Wallace Cabral (Laboratório Editorial Faculdade de Ciências e Letras, 2017)
The study on screen aims to present a brief discussion about the sociological interpretations of Giddens and Bauman regarding modernity. The authors differ in regard to the consequences of modernity in human interactions, for Giddens advanced modernity brought autonomy to individuals; for Bauman, liquidi modernity brought individualism and cooling in interpersonal relationships. The present text will present some theoretical and methodological elements mobilized by each author to characterize the institutional configurations in the contemporaneity.